Dynamics of intercultural communication: Papuans in Gorontalo - Sawedy, Riska M; Sarwono, Billy (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
This research discusses the dynamics of communication between two different cultural groups applied by ten Papuan student informants in Gorontalo and at the same time identifies that Gorontalo, which according to the researcher's observations has no cases, information, incidents of discrimination against Papuans, has the possibility of discrimination. This research uses Mark Orbe's Co-cultural theory with an interpretive phenomenological analysis study. The results of the research show that the minority group of Papuan students in Gorontalo uses communication dynamics using accommodation, which is a form of establishing good ties with the majority group without losing the original identity of Papuans. Assimilation is also the second dominant dynamics used by Papuan students in Gorontalo, namely adopting the culture of the dominant group. And there is discrimination in the Gorontalo area even though there are no records, cases or even official information.